Fatty liver index predicts incident risk of prediabetes, type 2 diabetes and non-alcoholic fatty liver disease (NAFLD). (1st January 2021) - Cuthbertson, Daniel J.; Koskinen, Juha; Brown, Emily; Magnussen, Costan G.; Hutri-Kähönen, Nina; Sabin, Matthew; Tossavainen, Päivi; Jokinen, Eero; Laitinen, Tomi; Viikari, Jorma; Raitakari, Olli T.; Juonala, Markus
Abstract: Aims: To investigate the association between overweight/obesity and fatty liver index (FLI) on the odds of incident prediabetes/type 2 diabetes and non-alcoholic fatty liver disease (NAFLD) in 2020 participants after 10 years follow up. Methods: At baseline (in 2001) 2020 participants, males and females, aged 24–39 years, were stratified according to body mass index (BMI), normal weight (<25 kg/m 2 ), overweight (≥25–<30 kg/m 2 ), or obese (≥30 kg/m 2 ) and FLI (as high FLI ≥60 or low FLI <60). We examined the incidence of prediabetes/type 2 diabetes and NAFLD (ultrasound assessed) over 10 years to 2011 to determine the relative impact of FLI and BMI. Results: 514 and 52 individuals developed prediabetes and type 2 diabetes during follow-up. Such individuals were older, with higher BMI, serum glucose, insulin, alanine aminotransferase (ALT) and triglyceride (TG) concentrations than those who did not develop prediabetes or type 2 diabetes ( n = 1454). The additional presence of high FLI significantly increased the risk of developing prediabetes and type 2 diabetes above the risk of being overweight/obese. Compared with normal weight, low FLI participants, the odds of prediabetes were ∼2-fold higher and the odds of type 2 diabetes were 9–10-fold higher respectively in the overweight/obese, high FLI group. No difference was observed between normal weight, low FLI and overweight/obese and low FLI groups. Conclusions: An increased FLI significantly increases the odds of incident prediabetes, type 2 diabetes and NAFLD in individuals with overweight/obese highlighting the contributory role of liver fat accumulation in the pathophysiology of prediabetes/type 2 diabetes. Key messages: Obesity is a risk factor for non-alcoholic fatty liver disease (NAFLD), prediabetes and type 2 diabetes. Additionally, NAFLD is more prevalent in people with prediabetes and type 2 diabetes when compared to age- and BMI-matched individuals. The presence of a raised fatty liver index (FLI) confers a significantly increased risk of developing prediabetes, type 2 diabetes and NAFLD above that conferred by being overweight/obese. The degree of elevation of FLI can risk stratify for incident prediabetes and type 2 diabetes in people with obesity.